Directors' Social Identifications and Board Tasks: Evidence from Finland. (13th November 2014) - Melkumov, Dmitri; Breit, Eric; Khoreva, Violetta
Abstract Manuscript Type Empirical Research Question/Issue Scholars and practitioners have been interested in the tasks of boards of directors, yet we know relatively little about the impact of directors' social identification on their engagement in specific board tasks. Examining the 92 largest Finnish industrial organizations, we explore how the directors' identification with the organization, its shareholders, and customers affects the extent to which the board engages in external legitimacy, networking, advice and counsel, top management monitoring, financial monitoring, strategic participation, and strategic evaluation tasks. Research Findings/Insights Following the social identity perspective, we provide new insight to understand the relationship between board tasks and the directors' relevant identifications. We find that organizational identification is positively related to the level of board task involvement. We also discover that shareholder identification is negatively related to strategic participation tasks and only weakly related to other board tasks. Theoretical/Academic Implications We contribute to the present literature on boards of directors by applying an empirical, analytical lens to theories on how and why directors engage in board tasks. In particular, we show that different social identifications of the directors have different explanatory power towards the subsets of resource provision and monitoring tasks. Practitioner/Policy Implications Our findings suggest a re‐evaluation of the shareholder supremacy view as the only driver of value creation for the organization. Additionally, we advocate that board, organization, and industry characteristics are similarly weak in predicting the involvement of the directors in the board tasks examined.